Research on the Challenges and Pathways to Breakthroughs in the Development of Consumer Finance in China - Liu, Zirong; Yuan, Siyuan (Asia Pacific Economic and Management Review, 2026)
As a key link connecting the financial system with real-world consumption, consumer finance serves as a vital financial pillar for expanding domestic demand, promoting consumption upgrades and driving high-quality economic development. In recent years, China’s consumer finance sector has undergone a profound transformation, shifting from explosive growth to a phase of standardisation. A diverse range of players—including licensed institutions, commercial banks and internet platforms—have collectively built a vast market ecosystem, with digitalisation and scenario-based services becoming increasingly prominent. However, against a complex backdrop of comprehensive regulatory tightening, falling interest rate caps, macroeconomic pressures and intensifying industry competition, China’s consumer finance sector faces multiple developmental challenges, including high funding costs, inadequate risk control systems, pressures from multiple borrowing and asset quality, compliance risks associated with loan facilitation models, severe product homogenisation, a lagging credit reporting system and insufficient consumer rights protection. Based on the latest developments in China’s consumer finance sector, this paper systematically analyses the industry’s deep-seated challenges. By integrating the latest regulatory policies with trends in fintech, it proposes targeted solutions across dimensions including compliant operations, enhanced risk management, deepening engagement with specific scenarios, optimised financing, improved credit reporting, consumer protection and differentiated transformation, with the aim of promoting the sustainable and high-quality development of China’s consumer finance industry.